KOMODITAS UNGGULAN DAN DAYA SAING SEKTOR PERTANIAN DI KABUPATEN TANAH DATAR - Marisa Nurmayenti; Syahrial Syahrial; Alvindo Dermawan (Jurnal Agribisnis Indonesia, 2023)
The agricultural sector has an important role in economic development. Determination of superior commodities in an area is the first step of development based on the concept of comparative and competitive advantage. This study aims to (1) analyze the leading commodities in Tanah Datar Regency (2) analyze the competitiveness of the leading commodities in Tanah Datar Regency (3) analyze the specialization and localization of superior commodities in Tanah Datar Regency. This research uses Location Quotient analysis, Dynamic Location Quotient, Shift Share Analysis, Specialization Quotient and Localization Quotient. The data used are secondary data, namely the production of the food crop sub-sector, horticulture sub-sector, and plantation sub-sector from 2016 to 2020. The results of the analysis show that (1) the percentage of agricultural sector commodities that are superior in Tanah Datar Regency is 40 percent, with the percentage of potential future superior commodities in Tanah Datar Regency is 63 percent (2) the percentage of competitive superior commodities in Tanah Datar Regency is 47 percent (3) the percentage of specialization and localization of superior commodities is 21 percent. From the results of the analysis, it is hoped that the government will direct the development of the agricultural sector with a focus on efforts to increase productivity, develop, and socialize superior agricultural commodities.